THE ROLE AND IMPORTANCE OF INFORMATION IN SOCIETY. - Tuganova Luiza Djuraevna; Nurymbetova Zumrad Ruslanovna (TADQIQOTLAR.UZ, 2024)
Abstract The article analyzes the changes that have occurred in public life and legal relations during the period of rapid development and introduction of information and communication technologies. Based on the presented facts and observations, the need for regulatory regulation of human actions and statements on the Internet, social and local networks is justified. In addition, it is concluded that information in modern society acquires increased value, since it can be used not only as a commodity, but also as a means of influencing society and state institutions as a whole.